Psychometric properties of the arabic version of the summary of diabetes self-care activities instrument - Sukkarieh-Haraty, Ola (2016)
Translation of instruments needs to ensure equivalence between the source and the target language to establish the psychometric properties of the translated version. The purpose of this study was to examine the psychometric properties of the Arabic version of the Summary of Diabetes Self-Care Activities (SDSCA) instrument. The 12-item English version of the SDSCA was translated into Arabic using back translation on a sample of 140 Lebanese participants with Type 2 diabetes. Construct validity was measured using exploratory factor analysis with varimax rotation. Multitrait scaling analysis was used to test for item convergent and discriminant validity based on item–scale correlations. Conceptual and content validity were examined by an expert panel in diabetes. Internal consistency reliability R was assessed using interitem correlations. The average interitem correlation for the four subscales ranged between – .05 for Diet and .66 for Glucose Testing. Factor analysis identified four factors which accounted for 60% of the variance. The preliminary results of Summary of Diabetes Self-Care Activities-Arabic Version (SDSCA-Ar) are comparable to the psychometric properties the original SDSCA. SDSCA-Ar is a valid measure of diabetes self-care in Lebanese patients with diabetes.